A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India - Yang, Chien-Hui; Kumar, Appukuttannair Biju; Chan, Tin-Yam (Zootaxa, 2017)
A new species of slipper lobster of the genus Petrarctus Holthuis, 2002 was discovered from southwestern India during a survey of deep sea crustaceans. The new species closely resembles P. veliger Holthuis, 2002 from the Andaman Sea and western Pacific but differs mainly in the color marking on abdominal somite I, having a relatively lower cardiac tooth but with better developed tubercles on the abdomen, as well as a differently shaped anterior part of the thoracic sternum. Molecular genetic analysis also confirms the distinct taxonomic status of the new species. To fix the identity of the type species of the genus, a neotype of P. rugosus (H. Milne Edwards, 1837) was selected from a recently collected Indian specimen with color and genetic information.